Respostas
respondido por:
6
x^2 - 2x = - 1
x^2 - 2x + 1 = 0
∆ = 4 - 4 = 0
x' = (2 + 0)/2 = 1
x" = (2 - 0)/2 = 1
Fórmulas:
∆ = b^2 - 4ac
x' = (- b + √∆)/2a
x" = (- b - √∆)/2a
x^2 - 2x + 1 = 0
∆ = 4 - 4 = 0
x' = (2 + 0)/2 = 1
x" = (2 - 0)/2 = 1
Fórmulas:
∆ = b^2 - 4ac
x' = (- b + √∆)/2a
x" = (- b - √∆)/2a
respondido por:
0
x^2 - 2x = -1
x^2 - 2x + 1 = 0
(x-1)*(x-1) = 0
x - 1 = 0/x-1
x - 1 = 0
x = 1
x^2 - 2x + 1 = 0
(x-1)*(x-1) = 0
x - 1 = 0/x-1
x - 1 = 0
x = 1
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás